Juvenile X-Linked retinoschisis: Response to topical dorzolamide therapy - Krati Gupta; Dipankar Das; Harsha Bhattacharjee; Hemalata Deka; Damaris Magdalene; Saurabh Deshmukh (TNOA Journal of Ophthalmic Science and Research, 2018)
We report clinical course of a 22-year-old Indian male patient presenting with bilateral Juvenile X-linked retinoschisis (JXLRS) in response to topical 2% dorzolamide hydrochloride treatment. He presented with progressive diminution of vision in both eyes (OU) for the past 16 years. A “cartwheel” macular pattern was observed in his retina OU. Multimodal imaging including fundus photography, fluorescein fundus angiography, optical coherence tomography (OCT), and electroretinogram was performed. Following treatment with topical dorzolamide, there was a significant regression of the macular cyst on OCT and significant improvement in the visual acuity. This case report emphasizes on the response of macular cysts to topical dorzolamide. Thus, it may be a promising treatment option in terms of visual as well as anatomical recovery in JXLRS.